Unveiling hidden reaction kinetics of carbon dioxide in supercritical aqueous solutions - Chu Li; Yuan Yao; Ding Pan (Proceedings of the National Academy of Sciences, 2025)
Dissolution of CO 2 in water followed by the subsequent hydrolysis reactions is of great importance to the global carbon cycle, and carbon capture and storage. Despite numerous previous studies, the reactions are still not fully understood at the atomistic scale. Here, we combined ab initio molecular dynamics (AIMD) simulations with Markov state models to elucidate the reaction mechanisms and kinetics of CO 2 in supercritical water both in the bulk and nanoconfined states. The integration of unsupervised learning with first-principles data allows us to identify complex reaction coordinates and pathways automatically instead of a priori human speculation. Interestingly, our unbiased modeling found an unknown pathway of dissolving CO 2 (aq) under graphene nanoconfinement, involving the pyrocarbonate anion [C 2 O 5 2 − (aq)] as an intermediate state. The pyrocarbonate anion was previously hypothesized to have a fleeting existence in water; however, our study reveals that it is a crucial reaction intermediate and stable carbon species in the nanoconfined solutions. We even observed the formation of pyrocarbonic acid [H 2 C 2 O 5 (aq)], which was unknown in water, in our AIMD simulations. The unexpected appearance of pyrocarbonates is related to the superionic behavior of the confined solutions. We also found that carbonation reactions involve collective proton transfer along transient water wires, which exhibits concerted behavior in the bulk solution but proceeds stepwise under nanoconfinement. The first-principles Markov state models show substantial promise for elucidating complex reaction kinetics in aqueous solutions. Our study highlights the importance of large oxocarbons in aqueous carbon reactions, with great implications for the deep carbon cycle and the sequestration of CO 2 .